Biodegradable and Compostable Plastics: A Critical Perspective on the Dawn of their Global Adoption. Issue 1 (17th December 2019) - Ciriminna, Rosaria; Pagliaro, Mario
Abstract: The global adoption of biodegradable and compostable plastics obtained from biomass‐derived monomers, we argue in this account, is now close to the inflection point. The first industrially significant impact will affect the packaging segment of the global chemical industry. In this process, China and India will play a pivotal role. Selected guidelines aiming to foster development of bioplastics industry in both developed and developing nations are provided. Abstract : Plastic – Quo vadis ? Estimates for biodegradable and compostable plastics market growth until 2025 suggest a modest yearly growth of less than 1 %. Yet, the bioplastics market will experience a production and uptake growth curve similar to that of photovoltaic solar cells since 2007, with China and India playing a pivotal role.